Gahnite-bearing marbles and their significance for regional classification of the eastern part of the Bohemian Massif - Novak,M.; Houzar,S.; Srein,V. (Journal of the Czech Geological Society, 1997)
Gahnite-bearing marbles in the Policka Unit and in the Hranicna Group were recognized as a distinct mineralogical and geochemical type of the marbles within the Bohemian Massif, typically rich in Zn and Mn (Fe). Gahnite seems to be the important Zn-carrier. Conditions of its origin are not explained sufficiently due to the simple mineral assemblages Cal+Dol+Tr+Phl+Di and its large stability field. The likely process of gahnite formation seems to be its crystallization from Zn, released during metamorphism from carbonate minerals, under conditions of a relatively high activity of Al in metamorphic fluids. Remarkably similar features of the studied marbles - lithology, chemical and mineral compositions, similar sulphide and Fe-oxide minerals, concentration and composition of gahnite - suggest the Policka Unit is closely related to the Hranicna Group (Stare Mesto Unit). Consequently, the Policka Unit may be lithologically a part of the Lugicum, which includes the Hranicna Group (Stare Mesto Unit).
Keywords: gahnite; marbles; chemical composition; regional classification; Policka Unit; Hranicna Group; Lugicum; Bohemian Massif